"Erosion" of Television City Hall Reporting? Perceptions of Reporters on the Beat in 2014 and 2001. (December 2017) - Riffe, Daniel; Abdenour, Jesse
Mail survey ( N = 112) of lead city government reporters at randomly selected television stations in the 210 local designated market areas replicates a 1997 study. The 2014 reporters had a more pessimistic view of station commitment to and valuing of city government reporting than in 1997 study. Among 2014 respondents, older reporters were more pessimistic whereas smaller market reporters were more optimistic, and a majority believes media commitment to covering city government remains generally strong.